Revision of Toxomerus Macquart, 1855 (Diptera: Syrphidae) from Brazil with synonymic notes, identification key to the species and description of three new species - Borges, Zuleica M.; Couri, Marcia S. (Zootaxa, 2009)
Toxomerus Macquart (Diptera: Syrphidae) species from Brazil are revised, including the examination of most of the types. Thirty six species are confirmed. Twenty seven are synonymized: T. dispar (Fabricius, 1794) [=T. vicinus (Macquart, 1846), T. tridentatus (Rondani, 1868) T. annulifer (Bigot, 1884), T. ruficaudatus (Bigot 1884), & T. triangulatus (Hull, 1942)], T. duplicatus (Wiedemann, 1830) [=T. vatius (Walker, 1852), T. gemini (Hull, 1941), T. arcturus (Hull, 1943), T. bipunctatus (Hull, 1943)], Syrphus basalis Walker, 1837 [=T. portius (Walker, 1852), T. rhea (Hull, 1949), T. harlequinus (Hull, 1951)], T. pictus (Macquart, 1842) [=T. jaguarinus (Bigot, 1884), T. maculatus (Bigot, 1884)], T. pulchellus (Macquart, 1846) [=T. punctatus Sack, 1921], T. virgulatus (Schiner, 1868) [=T. confusus (Schiner, 1868)], T. laenas (Walker, 1852) [=T. barbulus (Walker, 1852), T. nitidiventris (Curran, 1930), T. vitreus (Hull, 1941)], T. norma (Curran, 1930) [=T. mulio (Hull, 1941)], T. productus (Curran, 1930) [=T. triradiatus (Hull, 1942), T. camilla (Hull, 1951), T. cyrillus (Hull, 1951), T. vanessa (Hull, 1951)], T. watsoni (Curran, 1930) [=T. lanei (Hull, 1942)], T. steatogaster (Hull, 1941) [=T. steatornis (Hull, 1943)], T. idalius (Hull, 1951) [=T. eurydice (Hull, 1951)]. Two new combinations are presented: Mesogramma apegiensis Harbach, 1974 (=Toxomerus apegiensis) and Syphus basalis Walker, 1837 (= Toxomerus basalis); six new records for Brazil are included: T. difficilis (Curran, 1930), T. idalius (Hull, 1951), T. productus (Curran, 1930), T. purus (Curran, 1930), T. sylvaticus (Hull, 1943) and T. undecimpunctatus (Enderlein, 1938). Three new species are described: Toxomerus mosaicus, Toxomerus papaveroi and Toxomerus paraduplicatus.